PENGARUH KEPEMIMPINAN DAN BUDAYA TERHADAP KINERJA APARATUR PEMERINTAH DAERAH DI SEKRETARIAT DAERAH KABUPATEN MUSI BANYUASIN - Irfansyah, Ahmad; Asoka, Rano (Institut Rahmaniyah Sekayu, 2023)
The research aims to see the influence of leadership and culture on the performance of regional government officials in the regional secretariat of Musi Banyuasin Regency. The results of the research show that the performance of the apparatus at the Regional Secretariat of Musi Banyuasin Regency is seen from the aspect of effectiveness, namely understanding the tasks given to employees, the level of quality of service provided by the apparatus to the service user community as well as the relevance of activity programs implemented in the organization and also cultural factors and The leadership shown by leaders to employees through attitude and example as well as a high work ethic can influence the behavior of officers and provide motivation in order to provide services to the service user community to achieve the vision and mission of the Regional Secretariat of Musi Banyuasin Regency.